Desbaste de árvores e a relação com a transmissão da radiação fotossintecamente ativa, dinâmica da água no solo e produção de grãos em sistemas integrados - Aragão, Wesley Filipe Dutra Ximenes (2021)
The Integrated crop-livestock-forest (ICLF) is a production strategy that integrates different production systems in the same area, such as grain, fiber, meat, milk, agro-energy and timber. With ILPF the synergistic effects between the components of the agro-ecosystem are sought for the sustainability of the production unit, contemplating its environmental suitability and the economic viability of the production system. The modifications promoted by the presence of trees affect the local microclimate in ILPF systems, radiation interception and competition for water with agricultural components. To mitigate the possible impacts on the agricultural component, the management of the forest component is of paramount importance for the viability of the system. The removal of some plants from the row, or even the suppression of entire rows, can generate income for the producer, besides promoting the maintenance/recovery of the productive potential of crops grown between the rows of trees. Understanding the changes after management is essential for planning ICLF. Therefore, the objective of this work was to evaluate the effect of thinning on the productive response of soybeans and corn in ICLF. The experiment was conducted in the experimental field of Embrapa Agrossilvipastoril, in Sinop-MT. The treatments evaluated were single tillage (LAV), ICLF with single rows, systematically thinning the outer rows of the row in the fifth year (ICLF-S), ILPF with triple rows, selectively thinning 50% of the trees in the triple row in the fifth year and systematically thinning the outer rows in the eighth year of planting (ICLF-T) and planting eucalyptus (EUC). Photosynthetically active radiation (PAR) transmission, soil moisture, and grain yield data were collected in the treatments. In the treatments with ILPF, the data were collected in a transect perpendicular to the central row and compared with the values obtained in single tillage, in the 2016/17; 2017/18; 2018/19; 2019/20 crops. Spatial analysis of PAR and soil moisture data in ILPF was performed. The systematic thinning of trees increased the transmission of PAR in ICLF, allowing the recovery of grain yields to levels similar to the LAV treatment. It also reduced the competition for water in the region close to the stubble. The effect of this thinning is more intense in the first year of cultivation and lasts longer than selective thinning.